Reseña/Review (Prádanos, Luis I., “Postgrowth Imaginaries. New ecologies and counterhegemonic culture in post-2008 Spain”, Liverpool, Liverpool University Press, ISBN: 978-1-78694-134-3, 246 págs., 2018) - Almazán Gómez, Adrián (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2021)
Reseña/Review (Prádanos, Luis I., “Postgrowth Imaginaries. New ecologies and counterhegemonic culture in post-2008 Spain”, Liverpool, Liverpool University Press, ISBN: 978-1-78694-134-3, 246 págs., 2018)